Clinical Approach to Neuroendocrine Neoplasm Associated With Ovarian Teratoma - Opalińska, Marta; Sowa-Staszczak, Anna; Olearska, Helena; Ulatowska-Bialas, Magdalena; Gilis-Januszewska, Aleksandra; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2021)
Background: Neuroendocrine neoplasms are a heterogeneous group of cancers that develop from enterochromaffin cells of the diffuse endocrine system, with increasing incidence over the last years. Ovarian neuroendocrine tumors(NET) are rare neoplasms, comprising 0.1%of all ovarian neoplasms and less than 5%of all neuroendocrine tumors. They may arise alone (as monodermal, specialized teratoma – ovarian carcinoid)or as a part of other ovarian lesion: cystic mature or immature teratomas. Due to the rarity of such cases reported in the literature, there is no consensus on diagnostic and therapeutic procedures in this group of patients. Materials and methods: The group of 10patients at the age of 19 to 77 years (mean 42.8±17.9), diagnosed with unilateral NET within ovarian teratoma were analyzed. The histopathological type of tumor, progression free survival after surgical treatment and presence of hormonally active syndrome were assessed. Results: 70% of patients have mature cystic teratomas with NET component and 30%have monodermal teratoma (strumal carcinoid). All cases of monodermal teratomas were diagnosed in women at premenopausal age. Determined Ki67 ranged from 2% to 9%. Ninety percent of lesions stained positive for synaptophysin and chromogranin, while markers: CK20, CK7, TTF-1 and CDX2 were negative in all cases, which ruled out their metastatic nature. None of the patients presented with carcinoid syndrome. All followed-up patients remain progression-free. Conclusions: The prognosis and clinical behavior of NETs associated with ovarian teratomas are good with long progression-free survival. In the absence of guidelines on the length of follow-up we suggest to conduct it for at least 10years, as in other than ovarian NETs.